Lysis and direct detection of coliforms on printed paper-based microfluidic devices. Issue 23 (22nd September 2020) - Snyder, Sarah A.; Boban, Mathew; Li, Chao; VanEpps, J. Scott; Mehta, Geeta; Tuteja, Anish
Abstract : This article presents an integrated microfluidic coliform lysis and detection device featuring customizable omniphilic regions created by direct printing of omniphilic channels on an omniphobic, fluorinated paper. Abstract : Coliforms are one of the most common families of bacteria responsible for water contamination. Certain coliform strains can be extremely toxic, and even fatal if consumed. Current technologies for coliform detection are expensive, require multiple complicated steps, and can take up to 24 hours to produce accurate results. Recently, open-channel, paper-based microfluidic devices have become popular for rapid, inexpensive, and accurate bioassays. In this work, we have created an integrated microfluidic coliform lysis and detection device by fabricating customizable omniphilic regions via direct printing of omniphilic channels on an omniphobic, fluorinated paper. This paper-based device is the first of its kind to demonstrate successful cell lysing on-chip, as it can allow for the flow and control of both high and low surface tension liquids, including different cell lysing agents. The fabricated microfluidic device was able to successfully detect E. coli, via the presence of the coliform-specific enzyme, β-galactosidase, at a concentration as low as ∼10 4 CFU mL −1 . Further, E. coli at an initial concentration of 1 CFU mL −1 could be detected after only 6 hours of incubation. We believe that these devices can be readily utilized for real world E. coli contamination detection in multiple applications, including food and water safety.